2022
DOI: 10.1108/ilt-12-2021-0474
|View full text |Cite
|
Sign up to set email alerts
|

Electrical wear performance of copper matrix composites reinforced with hybrid CNTs and TiB2 particles

Abstract: Purpose Copper matrix composites are widely used in high-voltage switches, electrified railways and other electric friction fields. The purpose of this study is to improve its wear resistance and investigate the effect of hybrid carbon nanotubes (CNTs) and titanium diboride (TiB2) particles reinforced copper matrix composites on electrical wear performance. Design/methodology/approach CNTs and TiB2 particles were introduced into copper matrix simultaneously by powder metallurgy combined with electroless copp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…To further improve the arc erosion resistance and wear resistance of Al 2 O 3 /Cu composites, the team has done a lot of research in the past (Long et al , 2019; Jia et al , 2022; Guo et al , 2021; Yang et al , 2022). It was found that the addition of carbon materials could improve the lubricity and wear resistance of the composites while enhancing the resistance to arc erosion, so CF-Al 2 O 3 /Cu composites were designed and fabricated in this paper.…”
Section: Introductionmentioning
confidence: 99%
“…To further improve the arc erosion resistance and wear resistance of Al 2 O 3 /Cu composites, the team has done a lot of research in the past (Long et al , 2019; Jia et al , 2022; Guo et al , 2021; Yang et al , 2022). It was found that the addition of carbon materials could improve the lubricity and wear resistance of the composites while enhancing the resistance to arc erosion, so CF-Al 2 O 3 /Cu composites were designed and fabricated in this paper.…”
Section: Introductionmentioning
confidence: 99%
“…High-voltage switches are crucial control nodes in power systems, and copper contacts are one of the core executive components in high-voltage switches. During the use of high-voltage switches, the wear gap of the contacts can lead to abnormal discharge of the switch, which has a negative impact on the operation of power equipment [2,3]. Improving the surface strength of copper contacts can improve their wear resistance and is of great significance for enhancing the service life of high-voltage switches [4].…”
Section: Introductionmentioning
confidence: 99%